New insight into bacterial zoonotic pathogens posing health hazards to humans - Marcin Ciszewski; Tomasz Czekaj; Eligia Maria Szewczyk (Nofer Institute of Occupational Medicine, 2014)
This article presents the problem of evolutionary changes of zoonotic pathogens responsible for human diseases. Everyone is exposed to the risk of zoonotic infection, particularly employees having direct contact with animals, i.e. veterinarians, breeders, butchers and workers of animal products' processing industry. The article focuses on pathogens monitored by the European Centre for Disease Prevention and Control (ECDC), which has been collecting statistical data on zoonoses from all European Union countries for 19 years and publishing collected data in annual epidemiological reports. Currently, the most important 11 pathogens responsible for causing human zoonotic diseases are being monitored, of which seven are bacteria: Salmonella spp., Campylobacter spp., Listeria monocytogenes, Mycobacterium bovis, Brucella spp., Coxiella burnetti and Verotoxin- producing E. coli (VTEC) / Shiga-like toxin producing E. coli (STEC). As particularly important are considered foodborne pathogens. The article also includes new emerging zoonotic bacteria, which are not currently monitored by ECDC but might pose a serious epidemiological problem in a foreseeable future: Streptococcus iniae, S. suis, S. dysgalactiae and staphylococci: Staphylococcus intermedius, S. pseudintermedius. Those species have just crossed the animal-human interspecies barrier. The exact mechanism of this phenomenon remains unknown, it is connected, however, with genetic variability, capability to survive in changing environment. These abilities derive from DNA rearrangement and horizontal gene transfer between bacterial cells. Substantial increase in the number of scientific publications on this subject, observed over the last few years, illustrates the importance of the problem. Med Pr 2014;65(6):819-829